Comparative study of morphology and heterochromatin distribution in three oilseed species of Brassica L. - Akbar , Faria; Begum, Kazi Nahida (Journal of Bangladesh Academy of Sciences, 2022)
Morphological traits and nature of heterochromatins in interphase nuclei and prophase chromosomes of three oilseed species of Brassica L. (B. campestris, B. juncea, and B. napus) have been investigated in this study for morpho-cytotaxonomical evaluation. The three Brassica species displayed morphologically differences in the case of plant heights, size and the shape of upper and basal leaves, types of inflorescence and color of seeds, etc. After analyzing the staining properties of heterochromatins (nature and amount) in the interphase nuclei, it was unveiled that B. juncea had a simple chromocenter type of interphase nuclei and might be perceived as the most evolved one among the three species of Brassica. Moreover, the phylogenetic relationship derived from the mean values of morphological traits also manifested the distinct position of B. juncea than the other two studied species of Brassica. Therefore, the findings obtained in this study may be utilized as a feasible implementation of biosystematics for the identification and proper characterization of the three species of Brassica L. J. Bangladesh Acad. Sci. 45(2); 169-179: December 2021